Β‐Cyclodextrin Functionalized Nanoporous Graphene Oxides for Efficient Resolution of Asparagine Enantiomers. Issue 19 (13th August 2018) - Qie, Fengxiang; Guo, Jiahui; Tu, Bin; Zhao, Xing; Zhang, Yuchun; Yan, Yong
Abstract: Efficient resolution of racemic mixture has long been an attractive but challenging subject since Pasteur separated tartrate enantiomers in 19 th  century. Graphene oxide (GO) could be flexibly functionalized by using a variety of chiral host molecules and therefore, was expected to show excellent enantioselective resolution performance. However, this combination with efficient enantioselective resolution capability has been scarcely demonstrated. Here, nanoporous graphene oxides were produced and then covalently functionalized by using a chiral host material‐β‐cyclodextrin (β‐CD). This chiral GO displayed enantioselective affinity toward the l ‐enantiomers of amino acids. In particular, >99 % of l ‐asparagine (Asn) was captured in a racemic solution of Asn while the adsorption of d ‐enantiomer was not observed. This remarkable resolution performance was subsequently modelled by using an attach‐pull‐release dynamic method. We expect this preliminary concept could be expanded to other chiral host molecules and be employed to current membrane separation technologies and finally show practical use for many other racemates. Abstract : Chiral separation : Nanoporous chiral graphene oxides were produced to resolve chiral amino acids. These chiral GOs displayed enantioselective affinity toward the l ‐enantiomers. In particular, >99 % of l ‐asparagine (Asn) was captured in a racemic solution of Asn while the adsorption of d ‐enantiomer was not observed.